Inactivation of Plasmodium falciparum in whole blood using the amustaline and glutathione pathogen reduction technology. Issue 4 (4th March 2020) - Sow, Cissé; Laughhunn, Andrew; Girard, Yvette A.; Lanteri, Marion C.; Amar El Dusouqui, Soraya; Stassinopoulos, Adonis; Grellier, Philippe
Abstract : BACKGROUND: Risk of transfusion‐transmitted (TT) malaria is mainly associated with whole blood (WB) or red blood cell (RBC) transfusion. Risk mitigation relies mostly on donor deferral while a limited number of countries perform blood testing, both negatively impacting blood availability. This study investigated the efficacy of the pathogen reduction system using amustaline and glutathione (GSH) to inactivate Plasmodium falciparum in WB. STUDY DESIGN AND METHODS: WB units were spiked with ring stage P. falciparum infected RBCs. Parasite loads were measured in samples at time of infection, after 24 hours at room temperature (RT), and after a 24‐hour incubation at RT post‐treatment with 0.2 mM amustaline and 2 mM GSH. Serial 10‐fold dilutions of the samples were inoculated to RBC cultures and maintained up to 4 weeks. Parasitemia was quantified by cytometry. RESULTS: The P. falciparum viability assay has a limit of detection of a single live parasite per sample. Input parasite titer was >5.7 log10 TCID50 per mL. A 24‐hour incubation at RT paused parasite development in controls, but they retained viability and infectivity when tested in culture. In contrast, no infectious parasites were detected in the amustaline/GSH‐treated sample after 4 weeks of culture. CONCLUSION: A robust level of P. falciparum inactivation was achieved in WB using amustaline/GSH treatment. Parasite log reduction was >5.7 log10 TCID50 per mL. Development of such a pathogen reduction system may provide an opportunity to reduce the risk of TT malaria and improve blood availability.